2012
DOI: 10.1007/s10397-012-0745-5
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal cuff dehiscence in laparoscopic hysterectomy: influence of various suturing methods of the vaginal vault

Abstract: Vaginal cuff dehiscence (VCD) is a severe adverse event and occurs more frequently after total laparoscopic hysterectomy (TLH) compared with abdominal and vaginal hysterectomy. The aim of this study is to compare the incidence of VCD after various suturing methods to close the vaginal vault. We conducted a retrospective cohort study. Patients who underwent TLH between January 2004 and May 2011 were enrolled. We compared the incidence of VCD after closure with transvaginal interrupted sutures versus laparoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 22 publications
1
62
0
2
Order By: Relevance
“…In literature, majority of the studies reported that vaginal cuff dehiscence after robotic and laparoscopic hysterectomy is higher than that after vaginal hysterectomy [4,6,12,13]. Studies comparing cuff dehiscence after minimal invasive procedures report cumulative cuff dehiscence 1/632, 1/200 and 1/60 for vaginal hysterectomies, lapaorscopic hysterectomies and robotic hysterectomies, respectively [9].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, majority of the studies reported that vaginal cuff dehiscence after robotic and laparoscopic hysterectomy is higher than that after vaginal hysterectomy [4,6,12,13]. Studies comparing cuff dehiscence after minimal invasive procedures report cumulative cuff dehiscence 1/632, 1/200 and 1/60 for vaginal hysterectomies, lapaorscopic hysterectomies and robotic hysterectomies, respectively [9].…”
Section: Discussionmentioning
confidence: 99%
“…4,5,10 Both laparoscopic and, in particular, robotic-assisted laparoscopic hysterectomies were associated with higher odds of dehiscence. These findings correlate with the available literature 1,12,13 and may reflect the accumulation of more experience with laparoscopic hysterectomy than with robotic-assisted hysterectomy at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors are ill-defined 5 and include factors that influence wound healing, as well as mechanical factors such as early resumption of sexual activity, trauma, and increased intra-abdominal pressure. [5][6][7][8][9] Limited data exist about the effect of different approaches to colpotomy creation, suture materials, 2 or suturing techniques 10,11 on the risk of vaginal cuff separation. 12 Furthermore, the available retrospective reports often lack clear descriptions of the technique of colpotomy used, especially in abdominal and vaginal hysterectomies.…”
Section: Introductionmentioning
confidence: 99%
“…Such an adverse effect mainly depends on the closing technique used on the vaginal cuff [16,17], the suture material used [17,18], and finally, the type of energy used for the colpotomy and the hemostasis of the vaginal cuff [19][20][21][22]. Blikkendaal [7] published a retrospective study in which he describes the incidence of vaginal cuff dehiscence in patients after a total laparoscopic hysterectomy. He also compares the vaginal cuff closure transvaginally with a laparoscopic approach, using Vicryl interrupted sutures and continuous barbed sutures.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, the rate of complications of vaginal cuff closure post laparoscopic hysterectomy ranges from 0 to 5% [4,5], the most common complications being: vaginal bleeding, dehiscence of the vaginal cuff and infection. Numerous strategies were undertaken in order to decrease such complications [6,7]. One solution has been the introduction of the unidirectional barbed suture for vaginal cuff closure.…”
Section: Introductionmentioning
confidence: 99%